Energigéo - Claire List (EchoGéo)
ENERGIGEO is a documentary application which allows an interactive exploration of a bibliographic corpus, issued from the International Geographical Bibliography, IGB, and from a collection of photographies given by the researchers and engineers of the PRODIG research unit, on the topic : The energy sources.